5‐Amino‐3, 4‐dinitropyrazole as a Promising Energetic Material. Issue 6 (22nd July 2016) - Muravyev, Nikita V.; Bragin, Anatoly A.; Monogarov, Konstantin A.; Nikiforova, Anna S.; Korlyukov, Alexander A.; Fomenkov, Igor V.; Shishov, Nikolay I.; Pivkina, Alla N.
Abstract: The nitrogen‐rich energetic compound 5‐amino‐3, 4‐dinitropyrazole (5‐ADP) was investigated using complementary experimental techniques. X‐ray diffraction indicates the strong intermolecular hydrogen bonding in 5‐ADP crystals. Compound exhibits low impact sensitivity (23 J) and insensitivity to friction. The activation energy of thermolysis determined to be 230±5 kJ mol −1 from DSC measurements. Accelerating rate calorimetry indicates the lower thermal stability (173 °C) of 5‐ADP than that of RDX, which is probably the main concern about using this compound. 5‐ADP also exhibits good compatibility with common energetic materials (viz. TNT, RDX, ammonium perchlorate), including an active binder. The burning rate of 5‐ADP monopropellant is higher than that of benchmark HMX, while the pressure exponent 0.51±0.04 is surprisingly low. Addition of ammonium perchlorate does not affect the pressure exponent of 5‐ADP, while the burning rate increases. The 5‐amino‐3, 4‐dinitropyrazole exhibits a notable combination of combustion performance, low sensitivity, and good compatibility, which renders it as a promising energetic material. Abstract :